Socio-Cultural issues of India in Kiran Desai’s Hullabaloo in the Guava Orchard - Dr. Ankitaben Anilkumar Desai (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Kiran Desai is an Indian English writer who won the Bookers Prize in 2006 for her second novel, The Inheritance of Loss (2006). In her stories, she portrayed Indian culture and society. She also showed post-colonial India through her novels. Her novels deal with the issue of an identity crisis, alienation, migration, globalization, etc. Desai's first novel Hullabaloo in the Guava Orchard was published in 1998. It is a story of an Indian middle-class family. The story revolves around Sampath Chawla, the protagonist, and his struggle to find his identity. The present paper attempts to study the socio-cultural issues of typical Indian society in the context of this novel. It focuses on the struggle of the protagonist and the causes of his displacement to the guava orchard. It shows how a young man displaces and becomes a hermit overnight. It also shows the protagonist's attempts to escape from his family, society, and problems. Instead of facing the issues and reality of life, Sampath-the protagonist runs from it and tries to find peace in the guava orchard.